Aspectos da biologia reprodutiva de Syrigma sibilatrix (Ardeidae, Aves) - Gussoni, Carlos Otávio Araujo [UNESP]; Guaraldo, André de Camargo [UNESP]; Staggemeier, Vanessa Graziele [UNESP] (My University, 2006)
A nest (12.7 m height) of Syrigma sibilatrix was studied on the campus of UNESP Rio Claro (São Paulo, Brazil). The nest was in a fork in the tree Machaerium nyctitans (Leguminosae). Focal observations (n = 103 h) were carried out from 13 September 2004 to 1 November 2004. The male and female both participated in nest building, which took 37 days, mainly between 05:00h - 11:00h. Sticks for the nest were collected at the rate of 5.7 ± 3.4 sticks hour -1, most by the male. The nest included 197 sticks, and was a fl at platform with diameter = 75cm, and depth = 14 cm. A single egg was laid and was incubated (by both sexes) for 66h57 (92% of the time of permanence of the individuals in the nest). The egg was moved 97 times (1.34 times/hour). A strong storm caused the egg to fall, interrupting the study.
Aspects of the reproductive biology of Syrigma sibilatrix (Ardeidae, Aves)
Keywords: Nest; Reproductive biology; Whistling Heron; egg; legume; nest structure; reproductive biology; wader; Brazil; Rio Claro; Sao Paulo [Brazil]; South America; Ardeidae; Aves; Fabaceae; Machaerium; Syrigma sibilatrix